Information system with dynamic content - Dinis, Miguel Filipe Oliveira (2021)
Modern information systems have functional requirements that can vary significantly between organizations or regional contexts for the same application area. This results in the existence of multiple software versions and their respective data models. Traditional development methods are not very flexible and effective in dealing with the implementation of new requirements in a time frame. A simple addition of an information element in a graphical form requires a change in the data model and its action in the system’s tables, resulting in an undynamic process of creating content that must be stored in the database. With the advent of cloud computing, technological solutions have emerged that allow the development of applications using little or no code. These solutions can even be operated by end users with knowledge of the application domain. This dissertation aimed to design and implement a platform to create information systems with dynamic content. The result was a low cost multiplatform web solution that allows a fast, intuitive and dynamic content development, through the design of models from a visual interface, for users with no knowledge of software engineering. In technological terms, the platform integrates robust open-source solutions, which, associated with a metadata approach, allows an abstraction regarding the data persistence layer.